Crystallization behavior and electrical characteristics of Ga–Sb thin films for phase change memory. (10th March 2020) - Yin, Qixun; Chen, Leng
Abstract: In this work, we investigated the structural and conductivity stability of Ga–Sb thin films for phase change memory (PCM). The mass density and thickness change are significant for stability and reliability of PCM. The Ga–Sb thin films were deposited on SiO2 /Si (100) wafer using magnetron co-sputtering method. Phase identification revealed that nanoscale face center cubic structure GaSb and rhombohedral structure Sb formed in Ga–Sb thin films, the formation of phase Sb was more obvious in Ga20 Sb80 . Ga–Sb film exhibits an unusual behavior upon crystallization with less mass density and thickness change. The microstructure of Ga45 Sb55 thin films improved their structural (density and film thickness) characteristics: the crystal growth of {111} and {110} oriented grains in Ga–Sb thin films is obvious, the grains growth in Ga45 Sb55 thin films was more even and the bonding states in Ga–Sb thin films were more stable. In addition, the conductivity activation energy of Ga–Sb decreased with increasing Sb contents, thus the temperature stability of conductivity was improved. The structure transformation and conductivity activation energy of Ga–Sb phase change materials are in favor of mechanical stresses reduction and reliability enhancement of PCM. This study introduces the influence mechanism of structural and conductivity stability in Ga–Sb thin films and may provide reference for further testing in higher endurance performance phase change materials.